1984
DOI: 10.1111/j.1464-410x.1984.tb07166.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function in Prostatic Cancer Patients Treated with Radiotherapy, Orchiectomy or Oestrogens

Abstract: Sexual function in prostatic carcinoma patients was studied in 12 patients from each of three treatment groups: radiotherapy, orchiectomy and oestrogen treatment. Significant deterioration occurred in all groups. Although erectile potency was preserved in 9 of 12 patients treated with radiotherapy, 7 of these had a marked reduction in the frequency of sexual activity. Men subjected to orchiectomy or oestrogen treatment were seldom capable of having intercourse or of experiencing orgasm. However, oestrogen-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…In men with prostate cancer, the emotional strain of the disease is often compounded by the side effects of treatment, which have been reported to cause distress in the majority of the patients (5)(6)(7)(11)(12)(13)(14)(15)(16)(17)(18). In this taxing situation, one would hope that the proportion of men who can con de in others would be higher than that amongst the general male population owing to efforts by social contacts and healthcare personnel to offer emotional support and counselling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In men with prostate cancer, the emotional strain of the disease is often compounded by the side effects of treatment, which have been reported to cause distress in the majority of the patients (5)(6)(7)(11)(12)(13)(14)(15)(16)(17)(18). In this taxing situation, one would hope that the proportion of men who can con de in others would be higher than that amongst the general male population owing to efforts by social contacts and healthcare personnel to offer emotional support and counselling.…”
Section: Discussionmentioning
confidence: 99%
“…Being diagnosed with cancer can be a traumatic experience for many men (1) and has been reported to result in major depression in up to 25% of patients (2)(3)(4). For men diagnosed with prostate cancer the side effects of the available treatments also lead to distress in the majority of patients (5)(6)(7)(11)(12)(13)(14)(15)(16)(17)(18). It is not known to what extent middle-aged and elderly men share their emotional concerns, nor whether this proportion changes after the men have been diagnosed with prostate cancer due to efforts by healthcare personnel or others to offer emotional support.…”
mentioning
confidence: 99%
“…Hard data on fre quencies of sexual intercourse in elderly men with and without prostatism are scarce and may be different from one country to the other. Considering the major impor tance in English literature given to nerve-sparing tech niques of radical prostatectomy for cancer [4] and sexual function after other types of prostate cancer treatments [5], one has the impression that sexual potency is of large importance for most, even older men; that is, however, not fully true in the clinical experience in our country. We decided to study the sexual activity of patients before and after treatment for benign prostatic hypertrophy (BPH).…”
Section: Introductionmentioning
confidence: 71%
“…In an early study by Bergman et al, men who underwent orchiectomy were more likely to be incapable of intercourse or erections than men treated with radiotherapy or estrogen therapy [138]. Klotz et al reported that, of the 12 patients who were sexually active prior to initiation of DES therapy (out of 20 total), two remained potent on therapy [139].…”
Section: Sexual Dysfunctionmentioning
confidence: 99%